A Single Nucleotide Polymorphism Is Involved in Regulation of Growth and Spore Formation of Bacillus anthracis Pasteur II Strain - Liang, Xudong; Zhu, Jin; Zhao, Zhongzhi; Zheng, Feng; Zhang, Enmin; Wei, Jianchun; Ji, Yon; Ji, Yinduo (Frontiers in Cellular and Infection Microbiology, 2017)
Anthrax toxins and capsules, which are encoded by genes located on pXO1 and pXO2, respectively, are major virulence factors of Bacillus anthracis. Our previous studies demonstrated that exposure to high-temperatures is unable to abolish the pXO1 plasmid of the Pasteur II strain, but the growth of the strain was obviously slower than that of the Sterne strain and wild-type virulent strain. To elucidate a potential regulatory mechanism of slowing growth, we employed comparative genome and bioinformatic analysis and revealed a unique SNP (G to T) at the 143135bp position in pXO1 that is possibly involved in the mediation of growth of Pasteur II. However, the T to G mutation in groR did not result in any change of the amino acid sequence. A predominant nucleotide G existed at the 143135bp in pXO1 of 100 wild-type B. anthracis isolates and 9 isolates documented in GenBank, whereas T replaced G in pXO1 of the Pasteur II strain. Further analysis indicate that the SNP is located in a gene between 143042 bp and 143173 bp, and that it encodes a small protein of 43 amino acids and is termed as a growth regulator (GroR). Site-directed mutagenesis and gene deletion demonstrates that groR regulates the growth and spore formation of B. anthracis. Our results indicate that the pXO1 plasmid is involved in the regulation of growth and spore formation in B. anthracis.